Efficient Production of Polyhydroxyalkanoate Through Halophilic Bacteria Utilizing Algal Biodiesel Waste Residue - Dubey, Sonam; Mishra, Sandhya (Frontiers in Bioengineering and Biotechnology, 2021)
The objective of the current work was to investigate the potential of halophilic bacterial isolates for efficient utilization of crude glycerol from algal biodiesel waste into polyhydroxyalkanoates (PHAs) a green plastic. Screening of the isolates was directly done in algal biodiesel waste residue containing solid agar plates supplemented with Nile red. Crude glycerol is a biodiesel waste whose bioconversion into value-added products provides an alternative for efficient management with dual benefit. For the scale-up studies of PHAs, Halomonas spp. especially H. daqingensis was observed as a potential candidate growing well in 3% Algal biodiesel waste residue (ABWR), 5% NaCl supplementation at 35°C within 48 h of incubation. Maximum Cell dry weight (CDW) of 0.362 ± 0.001 g and 0.236 ± 0.003 g PHA was obtained with H. daqingensis when grown in the fermentor with 0.5 vvm air flow rate and 200 rpm containing 3% ABWR supplemented with 5% NaCl at 35°C incubation temperature for 48 h. ABWR can serve as a sole substrate for PHA production at an industrial scale serving two approaches: getting rid of the biodiesel industrial waste containing high amount of glycerol besides using waste replacing commercial substrate thereby reducing the cost of the product.